An Intramolecular CAr–H•••O=C Hydrogen Bond and the Configuration of Rotenoids - Ren, Yulin; Gallucci, Judith C.; Kinghorn, A. Douglas (Planta Medica, 2017)
Over the past half a century, the structure and configuration of the rotenoids, a group of natural products showing multiple promising bioactivities, have been established by interpretation of their NMR and electronic circular dichroism spectra and confirmed by analysis of single-crystal X-ray diffraction data. The chemical shift of the H-6′ 1H NMR resonance has been found to be an indicator of either a cis or trans C/D ring system. In the present study, four structures representing the central rings of a cis-, a trans-, a dehydro-, and an oxadehydro-rotenoid have been plotted using the Mercury program based on X-ray crystal structures reported previously, with the conformations of the C/D ring system, the local bond lengths or interatomic distances, hydrogen bond angles, and the H-6′ chemical shift of these compounds presented. It is shown for the first time that a trans-fused C/D ring system of rotenoids is preferred for the formation of a potential intramolecular C6′–H6′•••O=C4 H-bond, and that such H-bonding results in the 1H NMR resonance for H-6′ being shifted downfield.
Keywords: Millettia caerulea; Fabaceae; rotenoids; intramolecular CAr–H•••O=C H-bond; NMR spectra and electronic effects; conformation and configuration